Garantir le risque thérapeutique - Margeat, Henri (Assurances)

(untitled) (HEC Montréal, 1990)
A therapeutic risk may occur at any time before, during or after surgery, and its seriousness varies from case to case. Insurers offer coverages which now make it easier for victims to obtain compensation, pitting the advocates of the old school of thought who uphold the personal accident theory (« l’individuelle accidents ») against the advocates of modern thought who uphold advance payment, on recovery (« l’avance sur recours »). In his article, Henri Margeat, a director of UPA, strongly defends the latter.